The utility of neutrophil-to-lymphocyte ratio determined at initial diagnosis in predicting disease stage and discriminating between active and stable disease in patients with sarcoidosis: a cross-sectional study. Issue 6 (18th August 2022) - Alparslan Bekir, Sumeyye; Sonkaya, Esin; Ozbaki, Fatma; Aydogan Eroglu, Selma; Sertcelik, Lale; Duman, Dildar; Kavas, Murat; Agca, Meltem; Erdem, Ipek; Ozmen, Ipek; Boga, Sibel; Hazar, Armagan; et al.
ABSTRACT: Objective: To evaluate the utility of neutrophil–lymphocyte ratio (NLR) determined at initial diagnosis in predicting advanced disease stage and discriminating between active and stable disease in sarcoidosis. Methods: A total of 465 patients with biopsy-proven sarcoidosis (age: 47 years, 70.5% females) were included in this retrospective cross-sectional study. Data on patient demographics, sarcoidosis stage, clinical status (stable and active), anti-inflammatory treatments, complete blood count, and inflammatory markers including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR) and platelet/mean platelet volume (MPV) ratio were recorded. NLR values were compared by subgrouping the patients according to the stage of sarcoidosis and clinical status, while the receiver operating characteristics (ROC) curve was plotted to determine the role of NLR in the identification of disease activity with the calculation of area under the curve (AUC) and cutoff value via ROC analysis. Results: Overall, active, and stable disease was evident in 36 (7.8%) and 427 (92.2%) patients, respectively. Median NLR values were significantly higher in patients with active disease compared with stable disease (3.31 (2.34–4.31) vs. 2.29 (1.67–3.23), p = 0.005). Advanced sarcoidosis stage was associated with significantly higher NLR values at stages 0, I, II, III and IV, respectively (p = 0.001). ROC analysis revealed an NLR cutoff value of ≥2.39 (AUC (95% CI): 0.70 (0.62–0.79), p < 0.001) to discriminate between active and stable clinic with a sensitivity of 72.0% and specificity of 52.0%. The significantly higher percentage of patients with active vs. stable disease had NLR values ≥2.39 (74.0 vs. 47.0%, p = 0.002). Conclusion: Our findings indicate the potential utility of on-admission NLR values to predict the risk of advanced disease stage and to discriminate between active and stable disease in sarcoidosis. Measured via a simple, readily available, and low-cost test, NLR seems to be a valuable marker for monitoring disease activity and progression.